2017
DOI: 10.4163/jnh.2017.50.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weight, waist circumference, prevalence of obesity, and dietary factors associated with weight gain over 8 years in Korean adults: Longitudinal data from the Korean Genome and Epidemiology Study

Abstract: Purpose: The purposes of this study were to describe changes in weight, waist circumference (WC), and prevalence of obesity over 8 years as well as investigate demographic and dietary factors associated with weight gain in Korean adults. Methods: The Korean Genome and Epidemiology Study is an ongoing community-based longitudinal study, which was started in 2001~2002 and repeated every 2 years. Height, weight, and WC were measured, and demographic data and food intake information using the food frequency questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This differed from Western population characteristics, where 68–79% of participants gained weight of and 8.3–15% lost weight 5,6 . The 8‐year follow‐up results of the Korean Genome and Epidemiology Study cohort, which included adults aged 40–69 years, showed similar results to our study population: 23% experienced a BMI decrease of ≥1 kg/m 2 , and 19.5% experienced a BMI increase of ≥1 kg/m 2 24 . Additionally, most of our participants underwent corporate health check‐ups every 1–2 years and provided lifestyle modification advice based on the results.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This differed from Western population characteristics, where 68–79% of participants gained weight of and 8.3–15% lost weight 5,6 . The 8‐year follow‐up results of the Korean Genome and Epidemiology Study cohort, which included adults aged 40–69 years, showed similar results to our study population: 23% experienced a BMI decrease of ≥1 kg/m 2 , and 19.5% experienced a BMI increase of ≥1 kg/m 2 24 . Additionally, most of our participants underwent corporate health check‐ups every 1–2 years and provided lifestyle modification advice based on the results.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, Korean cohort studies showed that Korean adults tended to lose weight with age during longitudinal follow-up. 24,28 Therefore, there may be a limitation to assess the association between weight loss and development of ACRN in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When mean WC and TG were compared between groups with 50 to 54 and 55 to 59 years in the KNHANES population, they were not significantly different [ 24 ]. The Korean Genome and Epidemiology Study, which is a community-based longitudinal study and included 10,038 adults aged 40 to 69 years, reported that the mean WC increased by 1.71 and 1.85 cm in men and women, respectively, during the 8-year period [ 25 ]. Compared to findings from the general population, the progress of metabolic impairment, especially mean WC and TG, over 3 years was remarkable in middle-aged women with MetS in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean adult is deemed to be obese if the body mass index (BMI) is 25 (kg/m 2 ) or more. Over the past decade, obesity rates in Korean men and women have increased by 4.9% and 1.5%, respectively 6 . The prevalence of obesity varies with age and changes in body composition and resting metabolic rate (RMR), caused by aging 7 .…”
Section: Introductionmentioning
confidence: 99%